Cross-cultural anxiety, parental and partner attachments and their correlation with relationship satisfaction - Enayet, Safina Binte; Pervin, Mst Maleka (Dhaka University Journal of Biological Sciences, 2024)
The present study was designed to investigate the cross-cultural anxiety, parental attachment, partner attachment and their correlation with the relationship satisfaction. In this study, the data were collected by voluntary sampling method and a total of 434 participants were recruited. One-way ANOVA analysis showed that Americans, Bangladeshi, and English reported higher levels of anxiety in their life than Thai nationalities which indicated that Thai have more relationship satisfaction than other nationalities. Further analysis showed that there is a significant positive correlation between anxiety and avoidant attachment, anxious attachment, mother avoidant, mother anxious, father avoidant, father anxious. In the analysis of attachment style, it was found that father avoidant and mother avoidant attachment was higher than father anxious and mother anxious attachment with their children. Dhaka Univ. J. Biol. Sci. 33(1): 23-31, 2024 (January)